2023
DOI: 10.3390/rs15092441
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Key Drivers of Ecosystem Water-Use Efficiency in China’s Subtropical Forests Using an Improved Remote-Sensing-Driven Analytical Model

Abstract: The subtropical forests in China play a pivotal part in the global and regional carbon–water cycle and in regulating the climate. Ecosystem water-use efficiency (WUE) is a crucial index for understanding the trade-off between ecosystem carbon gain and water consumption. However, the underlying mechanisms of the WUE in forest ecosystems, especially the different subtropical forests, have remained unclear. In this paper, we developed a simple framework for estimating forest WUE and revealing the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
2
0
0
Order By: Relevance
“…At very high elevations (Qinghai‐Tibetan plateau), alpine meadow ecosystem is very sensitive to drought (M. Xu et al., 2021), making PRE and SM dominate NEP changes. Many studies have revealed that VPD affects vegetation more than SM (T. Chen et al., 2023; X. Wang et al., 2019), our study also reveals that VPD is more crucial than SM at lower elevations. However, at higher elevations, SM is more crucial than VPD due to the strong evaporation and shallow soils at high elevations (H. Y. Liu et al., 2018; Shi et al., 2014; You et al., 2020).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…At very high elevations (Qinghai‐Tibetan plateau), alpine meadow ecosystem is very sensitive to drought (M. Xu et al., 2021), making PRE and SM dominate NEP changes. Many studies have revealed that VPD affects vegetation more than SM (T. Chen et al., 2023; X. Wang et al., 2019), our study also reveals that VPD is more crucial than SM at lower elevations. However, at higher elevations, SM is more crucial than VPD due to the strong evaporation and shallow soils at high elevations (H. Y. Liu et al., 2018; Shi et al., 2014; You et al., 2020).…”
Section: Discussionsupporting
confidence: 76%
“…At very high elevations (Qinghai-Tibetan plateau), alpine meadow ecosystem is very sensitive to drought (M. Xu et al, 2021), making PRE and SM dominate NEP changes. Many studies have revealed that VPD affects vegetation more than SM (T. Chen et al, 2023;X. Wang et al, 2019), our study also reveals that VPD is more crucial than SM at lower elevations.…”
Section: Influence Of Elevation On the Response Of Net Ecosystem Prod...supporting
confidence: 69%